Factors Affecting Repurchase Intention Interest in Fashion E-Commerce in Batam City - Suyono Saputra; Micel Thai (Institute of Computer Science (IOCS), 2022)
Fashion is a style that is used daily by someone, where they can show their ideals and personalities. Therefore, nowadays, many customers buy back clothes online. This research was carried out to know the relationship between quality, value, innovativeness, brand awareness, trust in satisfaction and repurchase intention, satisfaction with repurchase intention, and brand awareness of repurchase intention through satisfaction. Likewise, the sample from this research is the Millennial/Y/Z generation in Batam City, which has obtained 252 data. Then, processing this sample data will use the SmartPLS version 26 software. The test data results in this study show that brand awareness, trust, and satisfaction with repurchase intentions have a significant positive effect, while quality, value, and innovativeness do not. Meanwhile, it shows that brand awareness, innovation, trust, and satisfaction value have a significant positive effect, while quality does not. Furthermore, the variable of brand awareness on repurchase intention through satisfaction is insignificant.